AAV-Txnip prolongs cone survival and vision in mouse models of retinitis pigmentosa - Yunlu Xue; Sean K Wang; Parimal Rana; Emma R West; Christin M Hong; Helian Feng; David M Wu; Constance L Cepko (eLife, 2021)
Retinitis pigmentosa (RP) is an inherited retinal disease affecting >20 million people worldwide. Loss of daylight vision typically occurs due to the dysfunction/loss of cone photoreceptors, the cell type that initiates our color and high-acuity vision. Currently, there is no effective treatment for RP, other than gene therapy for a limited number of specific disease genes. To develop a disease gene-agnostic therapy, we screened 20 genes for their ability to prolong cone photoreceptor survival in vivo. Here, we report an adeno-associated virus vector expressing Txnip, which prolongs the survival of cone photoreceptors and improves visual acuity in RP mouse models. A Txnip allele, C247S, which blocks the association of Txnip with thioredoxin, provides an even greater benefit. Additionally, the rescue effect of Txnip depends on lactate dehydrogenase b (Ldhb) and correlates with the presence of healthier mitochondria, suggesting that Txnip saves RP cones by enhancing their lactate catabolism.